THE EFFECT OF PROVIDING BREM DRUGS AS A SUBSTITUTION FOR CORN ON THE PERFORMANCE OF BROILER PRODUCTION - S., MUFIDAH; SJOFJAN, O.; DJUNAIDI, I. H. (Majalah Ilmiah Peternakan; Vol 27 No 2 (2024): Vol. 27 No. 2 (2024)DO - 10.24843/MIP.2024.V27.i02.p09, 2024)
This study aims to find out how producing broiler chickens performs when corn is replaced with brem dregs. The 200 Lohman MB 202 Platinum chicken strain, comprised of one-day-old unsexed chicks, was employed in the investigation. There were five treatments in Complete Random Design (CRD). P0, the control group, was fed untreated feed, whereas P1, P2, P3, and P4 were fed brem dregs in various amounts as a substitute for corn. Every treatment was carried out four times. The data were then statistically analyzed using analysis of variance (ANOVA) by a completely randomized design. Duncan’s multiple range test should be performed if the results show a signifi- cant difference (P<0.05) or a highly significant difference (P<0.01). The results showed that feed conversion, IOFC, body weight gain, and consumption were all significantly (P<0.01) impacted by the use of brem dregs. The results of this study demonstrate that brem dregs can be fed to broiler chickens in place of corn at feeding levels of up to 40%.